Ethnopharmacology Analysis of Antidiabetic Medicinal Plants from Menoreh Hills: Linking Local Knowledge to Pharmacological Evidence - Faisal Nur Arib; Kintoko Kintoko; Nanik Sulistyani; Akrom Akrom (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Abstract: The prevalence of type 2 diabetes mellitus (T2DM) has been increasing worldwide and in Indonesia. Documenting locally utilized antidiabetic plants may inform evidence-based phytotherapy. This study mapped antidiabetic medicinal plants in Samigaluh (Menoreh Hills) and prioritized candidates by linking community knowledge with pharmacological data. Semi-structured interviews and observation were conducted between July and August 2025, and involved ten informants selected through purposive and snowball sampling. Quantitative ethnobotanical indices (Use Value, Relative Frequency of Citation, Fidelity Level, Plant Part Value) were calculated, followed by a PubMed-based narrative review. The Zingiberaceae family was predominant (seven species); rhizomes were the most utilized (39.58%), followed by stems (25.00%) and leaves (22.92%). Vernonia amygdalina was prioritized for diabetes-specific consensus (Fidelity Level 100%, Relative Frequency of Citation 0.7), and Curcuma mangga for its high usage and popularity (Use Value 1.3, Relative Frequency of Citation 0.6). Pharmacological evidence indicates that V. amygdalina exhibits antidiabetic effects through the inhibition of α-amylase and α-glucosidase, enhancement of GLUT4, and suppression of gluconeogenesis, supported by its antioxidant and anti-inflammatory properties, while C. mangga demonstrates hypoglycemic activities and β-cell protection, along with anti-inflammatory, antioxidant, and immunostimulant activities as supportive mechanisms. Local knowledge thus aligns with mechanistic findings, supporting a complementary pairing of V. amygdalina and C. mangga for future antidiabetic combinations; further validation through in vitro and in vivo studies is recommended.